Resveratrol improves ischemia/reperfusion-induced oxidative renal injury in rats - ÇETİNEL, ŞULE (ELSEVIER SCIENCE INC, 2006)
Background. The present study was designed to examine whether resveratrol, a potent antioxidant, protects against renal ischemia-reperfusion (I/R) injury. Methods. Wistar albino rats were unilaterally nephrectomized and subjected to 45 min of renal pedicle occlusion followed by 6 h of reperfusion. Resveratrol (RVT, 30 mg/kg, i.p.) or vehicle was administered twice, at 30 min prior to ischemia and immediately before the reperfusion period. At the end of the reperfusion period, rats were decapitated and kidney samples were taken for histological examination or determination of levels of renal malondialdehyde (MDA), an end product of lipid peroxidation; glutathione (GSH), a key antioxidant; and myeloperoxidase (MPO) activity, an index of tissue neutrophil infiltration. Formation of reactive oxygen species in hepatic tissue samples was monitored by using chemiluminescence (CL) technique with luminol and lucigenin probes. Renal tissue collagen content as a fibrosis marker was also determined, while serum creatinine and urea concentrations were measured for the evaluation of renal function. Tumor necrosis factor-alpha (TNF-alpha) and lactate dehydrogenase (LDH) were also assayed in serum samples. Results. Ischemia/reperfusion caused a significant decrease in tissue GSH level, which was accompanied by significant increases in the renal luminol and lucigenin CL values, MDA level, MPO activity and collagen content. Similarly, serum creatinine and BUN levels, as well as LDH and TNF-alpha, were elevated in the I/R group as compared to control group. On the other hand, resveratrol treatment reversed all these biochemical indices, as well as histopathological alterations that were induced by I/R. Conclusions. Findings of the present study suggest that resveratrol exerts renoprotective effects via its radical scavenging and antioxidant activities, which appear to involve the inhibition of tissue neutrophil infiltration. (C) 2006 IMSS. Published by Elsevier Inc.
Keywords: ischemia/reperfusion; kidney; oxidative stress; resveratrol; MYELOPEROXIDASE ACTIVITY; FREE-RADICALS; RED WINE; STRESS; MECHANISMS; ISCHEMIA; GLUTATHIONE; MELATONIN; TISSUE; DAMAGE